2013
DOI: 10.1681/asn.2012080834
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Formin 2 Regulates Actin Dynamics by Antagonizing Rho/Diaphanous-related Formin Signaling

Abstract: Mutations in inverted formin 2 INF2 are a common cause of familial FSGS. INF2 interacts with diaphanousrelated formins (mDia) and antagonizes mDia-mediated actin polymerization in response to active Rho signaling, suggesting that dysregulation of these pathways may mediate the development of INF2-related FSGS. However, the precise mechanisms by which INF2 regulates actin-dependent podocyte behavior remain largely unknown. Here, we investigated the possible role of INF2 in both lamellipodia-associated actin dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 51 publications
8
68
1
Order By: Relevance
“…Therefore, direct binding between the INFT-2-DID and the CYK-1-DAD might also occur. Importantly, in the EC we found that CYK-1 inhibits the actinpolymerizing activity of INFT-2; the reciprocal effect to that seen in previous studies (Sun et al, 2013(Sun et al, , 2011. Whether this reciprocal effect can also be observed with human mDia and INF2 will require more precise in vitro and cell culture studies.…”
Section: Model For How the Exc-5−cdc-42 Pathway Regulates A Formin Nesupporting
confidence: 68%
See 4 more Smart Citations
“…Therefore, direct binding between the INFT-2-DID and the CYK-1-DAD might also occur. Importantly, in the EC we found that CYK-1 inhibits the actinpolymerizing activity of INFT-2; the reciprocal effect to that seen in previous studies (Sun et al, 2013(Sun et al, , 2011. Whether this reciprocal effect can also be observed with human mDia and INF2 will require more precise in vitro and cell culture studies.…”
Section: Model For How the Exc-5−cdc-42 Pathway Regulates A Formin Nesupporting
confidence: 68%
“…Scale bars: 10 µm (B,E); 5 µm (C,F). (Madrid et al, 2010); and CYK-1, the sole ortholog of mDia (MiMi et al, 2012), because a direct interaction between INF2 and mDia, modulated by Cdc42, had been described and found to regulate F-actin in cell culture (Sun et al, 2013(Sun et al, , 2011. In considering the relationship of the two C. elegans paralogs with INF2, we note that phylogenetic analysis clearly places INFT-2 in the same family as human INF2 (Mi-Mi et al, 2012;Fig.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations